How public owners communicate the sustainability requirements of green design-build projects - Xia, B.; Skitmore, M.; Wu, Peng; Chen, Q. (American Society of Civil Engineers (ASCE), 2014)
The design/build (DB) system is regarded as an effective means of delivering sustainable buildings. Specifying clear sustainability requirements to potential contractors is of great importance to project success. This research investigates the current state-of-the-practice for the definition of sustainability requirements within the public sectors of the U.S. construction market using a robust content analysis of 49 DB requests for proposals (RFPs). The results reveal that owners predominantly communicate their desired level of sustainability through the leadership in energy and environmental design (LEED) certification system. The sustainability requirement has become an important dimension for the best-value evaluation of DB contractors with specific importance weightings of up to 25%. Additionally, owners of larger projects and who provide less design information in their RFPs generally allocate significantly higher importance weightings to sustainability requirements. The primary knowledge contribution of this study to the construction industry is the reveal of current trends in DB procurement for green projects. The findings also provide owners, architects, engineers, and constructors with an effective means of communicating sustainability objectives in solicitation documents. © 2014 American Society of Civil Engineers.